THE PROTON PROMOTED DISSOLUTION KINETICS OF K-MONTMORILLONITE - Zysset M.; Schindler P.W. (My University, 1996)
The kinetics of proton promoted dissolution of K-montmorillonite was investigated at 298 ± 1 K by batch experiments in the range 10−1 ≥ [H+] ≥ 10−5 M using solutions of the constant KCl concentrations of 0.03 M, 0.10 M, and 1.0 M, respectively. In addition the concentration of adsorbed H+-ions (H+, [mol/g]) was determined in the acidic range using both titration and batch equilibration experiments. The dissolution rates RSi and RAl [mol/(g · h)] were obtained from the observed increase with time of both dissolved Si(IV) and Al(III). RSi was found to be linearly dependent on H+: RSi = k · H+.The values of the first order rate constant k [h−1] increase with increasing KCl concentration: 6.02 × 10−4 ± 2.4 × 10−5 h−1 (0.03 M KCl), 9.98 × 10−4 ± 7.1 × 10−5 h−1 (0.10 M KCl), and 2.61 × 10−3 ± 3.9 × 10−4 h−1 (1.0 M KCl). Adsorption of H+-ions was interpreted in terms of the surface complexation model. Proton uptake by the solid phase were formally attributed to H-K exchange and to protonation of edge surface aluminol groups. The dissolution reaction does, however, not discriminate between these two adsorption modes.At 0.10 M and 1.0 M KCl the observed ratio Q = RSi/RAl was found to be close to the Si:Al ratio in the solid phase, suggesting congruent dissolution. In 0.03 M KCl and [H+] > 3.2 × 10−2 M, Q exceeded the Si:Al ratio of the solid. This deviation from congruency at low KCl concentration was attributed to adsorption of dissolved Al(III) by cation exchanger sites as reported by Charlet et al. ( 1993b). Added Al(III) was found to inhibit the dissolution reaction at [H+] ≤ 10−3 M. Observations by Charlet et al. (1993b) suggest that this inhibition originates from adsorption of Al(III) on crystal edge surface sites. Both the observed dissolution stoichiometry and the inhibition by added Al(III) leads to the conclusion that dissolution occurs predominantely at the crystal edge surfaces.